Economical design procedures for built-up box sections subject to compression and bi-axial bending. (February 2015) - Bedair, Osama; Eng, P.
Abstract: The paper offers to practitioners economical procedures that can be utilized to optimize the design of built up box sections subject to compression and biaxial bending. Little emphasis appeared in the published literature that addressed this general loading condition. The analysis methodology and structural idealization are first overviewed. Diagrams are presented showing buckling behavior of the section by accounting rotational and lateral restraints. The post-buckling response is also illustrated for various applied stress ratios. A design space concept is then introduced showing interaction of serviceability and strength limit states. These procedures are cost effective and appropriate for industrial implementation to optimize the structural design.